2022
DOI: 10.3389/fmolb.2022.839806
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix-Based Gene Expression Signature Defines Two Prognostic Subtypes of Hepatocellular Carcinoma With Different Immune Microenvironment Characteristics

Abstract: Background: Accumulating evidence has suggested that the extracellular matrix (ECM) plays a vital role in the development and progression of cancer, and could be recognized as a biomarker of the response to immunotherapy. However, the effect of the ECM signature in hepatocellular carcinoma (HCC) is not well understood.Methods: HCC patients derived from the TCGA-LIHC dataset were clustered according to the ECM signature. The differences in prognosis, functional enrichment, immune infiltration, and mutation char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
(52 reference statements)
1
8
1
Order By: Relevance
“…Therefore, PDCL3 may serve as a relevant target in immunotherapy. Previous studies indicated that LIHC patients with high macrophage infiltration have a better prognosis [ 36 ], consistent with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, PDCL3 may serve as a relevant target in immunotherapy. Previous studies indicated that LIHC patients with high macrophage infiltration have a better prognosis [ 36 ], consistent with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…The principal cause of this difference was based on our selection of a lncRNA set that was coexpressed with ECM-related genes. Two signatures consisting of ECM-related genes have been previously reported [ 24 , 25 ]; however, these signatures were not equivalent to our lncRNA signature. Indeed, comprehensive studies were performed to evaluate the prognostic value of the models generated using these signatures, and these signatures also predicted the immune landscape as well as drug sensitivity.…”
Section: Discussioncontrasting
confidence: 59%
“…78 Research has identified six ECM-associated genes (namely SPP1, ADAMTS5, MMP1, BSG, LAMA2, and CDH1) that correlate with a dismal prognosis in HCC patients. 79 ECM is gradually remodeled by cancer cells in TME, which facilitates tumor development and metastasis. 80 MMPs are a class of zinc-dependent endoproteases that disrupt the ECM by destroying the structure of different proteins within it.…”
Section: Other Factors In Tme Ecmmentioning
confidence: 99%